2018
DOI: 10.1021/acs.orglett.8b02676
|View full text |Cite
|
Sign up to set email alerts
|

N-Arylation of DABCO with Diaryliodonium Salts: General Synthesis of N-Aryl-DABCO Salts as Precursors for 1,4-Disubstituted Piperazines

Abstract: Employing DABCO as a substrate, aryl(mesityl)iodonium triflates are introduced as arylating agents for a tertiary sp 3 -nitrogen. Mild conditions and exceptional selectivity of the aryl group transfer allow unprecedented N-aryl-DABCO salts to be obtained, bearing substituents of different electronic natures. This metal-free methodology has no analogy among known transition-metal-based reactions. The utility of isolated N-aryl-DABCO salts is demonstrated for the preparation of flibanserin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…The reaction of Ph3Sb with PhI(OAc)2 has been previously reported to oxidize the antimony and give the expected diacetoxy Sb(V) complex. 26 Colourless crystals were obtained and X-ray diffraction studies showed via unit cell analysis 27 the result was a diaryliodonium triflate salt 13 (Scheme 11) with 1 H NMR of the crystals also matching literature reports. 28 Compound 13 has been synthesised via numerous different methods one of which is known to involve a diarylstannane reagent.…”
Section: Resultssupporting
confidence: 67%
“…The reaction of Ph3Sb with PhI(OAc)2 has been previously reported to oxidize the antimony and give the expected diacetoxy Sb(V) complex. 26 Colourless crystals were obtained and X-ray diffraction studies showed via unit cell analysis 27 the result was a diaryliodonium triflate salt 13 (Scheme 11) with 1 H NMR of the crystals also matching literature reports. 28 Compound 13 has been synthesised via numerous different methods one of which is known to involve a diarylstannane reagent.…”
Section: Resultssupporting
confidence: 67%
“…Colourless crystals were obtained and X-ray diffraction studies showed via unit cell analysis 27 the result was a diaryliodonium triflate salt 13 (Scheme 11) with 1 H NMR of the crystals also matching literature reports. 28 Compound 13 has been synthesised via numerous different methods one of which is known to involve a diarylstannane reagent.…”
supporting
confidence: 81%
“…Recently, Karchava et al introduced the diaryliodonium salts 94 as efficient arylating agents for a tertiary sp 3 -nitrogen. 46 For this purpose, reaction of DABCO 1 (1 equiv.) with various aryl(mesityl)iodonium triflates 94 (2 equiv.)…”
Section: Diaryliodonium Triflates As Activating Agentsmentioning
confidence: 99%